Developing a Learning Evaluation Tool Based on the Gimkit Application on Economic Systems to Improve Student Learning Outcomes - Humaisaroh, Siti; Dewi, Retno Mustika (Journal of English Language and Education, 2026)
This study aims to develop a learning evaluation tool using the GimKit application on economic system material in Economics for grade X-6 and to analyze its feasibility, practicality, and effectiveness in improving student learning outcomes. Learning evaluation in schools is still dominated by the use of Student Worksheets (LKS), which tend to be monotonous, less interactive, and less optimal in measuring higher-order thinking skills. This condition contributes to low student learning outcomes and indicates the need for innovation in digital-based evaluation tools. This research uses the Research and Development (RD) method with the 4D development model consisting of define, design, develop, and disseminate stages. The subjects of this study were grade X students at SMAN 19 Surabaya. Data collection techniques included expert validation from material and media experts, practicality questionnaires, student response questionnaires, and pretest–posttest tests to measure cognitive learning outcomes. The results show that the GimKit-based evaluation tool is very feasible according to expert validation, practical to use in learning activities, and effective in improving student learning outcomes, as indicated by the increase in posttest scores compared to pretest scores. Therefore, the GimKit-based evaluation tool can be used as an innovative, interactive, and effective alternative for learning evaluation on economic system material.